Membrane-based carbon capture: Recent progress, challenges, and their role in achieving the sustainable development goals. (April 2023) - Olabi, A.G.; Alami, Abdul Hai; Ayoub, Mohamad; Aljaghoub, Haya; Alasad, Shamma; Inayat, Abrar; Abdelkareem, Mohammad Ali; Chae, Kyu-Jung; Sayed, Enas Taha
Abstract: The rapid growth in the consumption of fossil fuels resulted in climate change and severe health issues. Among the different proposed methods to control climate change, carbon capture technologies are the best choice in the current stage. In this study, the various membrane technologies used for carbon capture and their impact on achieving sustainable development goals (SDGs) are discussed. Membrane-based carbon capture processes in pre-combustion and post-combustion, which are known as membrane gas separation (MGS) and membrane contactor (MC), respectively, along with the process of fabrication and the different limitations that hinder their performances are discussed. Additionally, the 17 SDGs, where each representing a crucial topic in the current global task of a sustainable future, that are impacted by membrane-based carbon capture technologies are discussed. Membrane-based carbon capture technologies showed to have mixed impacts on different SDGs, varying in intensity and usefulness. It was found that the membrane-based carbon capture technologies had mostly influenced SDG 7 by enhancement in the zero-emission production, SDG 9 by providing 38–42% cost savings compared to liquid absorption, SDG 3 through reducing pollution and particulate matter emissions by 23%, and SDG 13, with SDG 13 being the most positively influenced by membrane-based carbon capture technologies, as they significantly reduce the CO2 emissions and have high CO2 capture yields (80–90%), thus supporting the objectives of SDG 13 in combatting climate change. Graphical abstract: Image 1 Highlights: Background about membrane-based CCT was introduced. Limitations of membrane-based CCT was elaborated. Membrane-based CCT positively influence SDG 13 by reducing 90% of the CO2 emissions in coal-based power plants. Membrane-based CCT impact SDG 9 by providing 38–42% cost savings compared to liquid absorption. Membrane-based CCT affect SDG 3 by reducing 23% of pollution and particulate matter emissions.